PENGISI BATERAI PORTABLE DENGAN MENGGUNAKAN SEL SURYA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2015)
Batteries are indispensable as the driving force or as a supply of energy on the use of electronic equipment. In certain circumstances the charging of the grid is a difficult, so we need a charger that can be taken anywhere (portable) without need of electricity grid, and therefore solar or solar power is used for this reason. The main components of this device is a solar cell (as an input to convert solar energy into electrical energy), battery charger circuit (as a controller), the LED indicator (as an indicator of charging battery), and battery (voltage 12 V). This tool is used when there is supply of energy from sunlight is converted into electrical energy through solar cells.